Extensive fragmentation of the X chromosome in the bed bug Cimex lectularius Linnaeus, 1758 (Heteroptera, Cimicidae): a survey across Europe - Sadílek, David; Sťáhlavský, František; Vilímová, Jitka; Zima, Jan (Comparative cytogenetics, 2013)
Variation in the number of chromosomes was revealed in 61 samples of Cimex lectularius Linnaeus, 1758 from the Czech Republic and other European countries, hosted on Myotis Kaup, 1829 (4) and Homo sapiens Linnaeus, 1758 (57). The karyotype of all the specimens of Cimex lectularius analysed contained 26 autosomes and a varying number of the sex chromosomes. The number of sex chromosomes showed extensive variation, and up to 20 fragments were recorded. Altogether, 12 distinct karyotypes were distinguished. The male karyotypes consisted of 29, 30, 31, 32, 33, 34, 35, 36, 37, 40, 42 and 47 chromosomes. The females usually exhibited the number of chromosomes which was complementary to the number established in the males from the same sample. However, 11 polymorphic samples were revealed in which the karyotypes of females and males were not complementary each other. The complement with 2n = 26+X1X2Y was found in 44% of the specimens and 57,4% samples of bed bugs studied. The karyotypes with higher chromosome numbers as well as individuals with chromosomal mosaics were usually found within the samples exhibiting particularly extensive variation between individuals, and such complements were not found within samples contaning a few or single specimen. The occurrence of chromosomal mosaics with the karyotype constitution varying between cells of single individual was observed in five specimens (4.3%) from five samples. We assume that polymorphism caused by fragmentation of the X chromosome may result in meiotic problems and non-disjunction can produce unbalanced gametes and result in lowered fitness of individuals carrying higher numbers of the X chromosome fragments. This effect should be apparently enhanced with the increasing number of the fragments and this may be the reason for the observed distribution pattern of individual karyotypes in the studied samples and the rarity of individuals with extremely high chromosome numbers. The assumed lowering of the fitness of individuals carrying higher numbers of the X chromosome fragments could affect population dynamics of variable populations.
Keywords: Cimex pipistrelli; chromosome number variation; cytogenetics; X chromosome; Cimex lectularius